2023
DOI: 10.1001/jamaoncol.2023.3748
|View full text |Cite
|
Sign up to set email alerts
|

Remotely Delivered Cancer Genetic Testing in the Making Genetic Testing Accessible (MAGENTA) Trial

Elizabeth M. Swisher,
Nadine Rayes,
Deborah Bowen
et al.

Abstract: ImportanceRequiring personalized genetic counseling may introduce barriers to cancer risk assessment, but it is unknown whether omitting counseling could increase distress.ObjectiveTo assess whether omitting pretest and/or posttest genetic counseling would increase distress during remote testing.Design, Setting, and ParticipantsMaking Genetic Testing Accessible (MAGENTA) was a 4-arm, randomized noninferiority trial testing the effects of individualized pretest and/or posttest genetic counseling on participant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Two exceptions to this, with similar findings, are a US study, reported by Swisher et al, that reported noninferiority of patient distress at three months and no statistically significant differences in anxiety, depression, or decisional regret between participants who did not have mandatory pre-test counselling (received information in the format of a video) compared to those who had pre-test genetic counselling (20). This study was outside of mainstream settings, for participants recruited from the public with a personal or family history of breast or ovarian cancer.…”
Section: Discussionmentioning
confidence: 57%
“…Two exceptions to this, with similar findings, are a US study, reported by Swisher et al, that reported noninferiority of patient distress at three months and no statistically significant differences in anxiety, depression, or decisional regret between participants who did not have mandatory pre-test counselling (received information in the format of a video) compared to those who had pre-test genetic counselling (20). This study was outside of mainstream settings, for participants recruited from the public with a personal or family history of breast or ovarian cancer.…”
Section: Discussionmentioning
confidence: 57%
“…This finding is not surprising given the tailored, expert communication and empathic exchanges that patients experience with CGCs. 25,40 However, only 1% of participants without PVs assigned to VE elected to meet with a CGC post-test despite ample opportunity to do so. Together with the fact that knowledge scores were not compromised in the VE arm, this low uptake of posttest GC may inform the prioritization of GC resources toward supporting patients and families with PVs.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in our findings may be explained by study design as interventions were in person (not online) or by study population as our participants were markedly different from the MAGENTA population (males, all had cancer and were approximately 20 years older). 25,40 Results from a nonrandomized, patient choice study of patients with PC found no differences in uptake of GT, knowledge, or decision regret with GT between VE and GC, and when offered a choice, patients selected VE. 41 This study, together with our data, demonstrates that a truncated approach to GT for this population is reasonable, in particular, as the identification of germline PV has become increasingly important for estimating prognosis and for treatment selection in oncology care.…”
Section: Discussionmentioning
confidence: 99%
“…Integrating point-of-care testing (defined as germline testing in the context of existing appointments with their medical or surgical oncology providers followed by post-test counseling with a genetics provider) into a similar workflow could allow genetics providers to focus their expertise where they may have the most impact. 14 In addition, potential germline pathogenic mutations are increasingly identified in the process of tumor-based sequencing and may require confirmatory germline testing and genetic counseling to assess patient risk. 15 Tumor-based sequencing is typically not designed to identify germline versus somatic origin of reported mutations.…”
mentioning
confidence: 99%
“…Integrating point-of-care testing (defined as germline testing in the context of existing appointments with their medical or surgical oncology providers followed by post-test counseling with a genetics provider) into a similar workflow could allow genetics providers to focus their expertise where they may have the most impact. 14…”
mentioning
confidence: 99%